Stimulant expectancy questionnaire for men who have sex with men: A measure of substance‐related beliefs. (3rd July 2019) - Mullens, Amy B.; Fein, Erich C.; Young, Ross McD.; Dunne, Michael P.; Norton, Graham; Daken, Kirstie
Abstract: Issue addressed: Stimulant use has been identified as a key risk factor for sexual behaviours leading to HIV transmission. Substance‐related expectancies are associated with substance use and postsubstance use thoughts, feelings and behaviours. Expectancies held by specific cultural subgroups have rarely been investigated, particularly regarding a range of commonly used stimulants. Method: The Stimulant Expectancy Questionnaire for Men who have Sex with Men (SEQ‐MSM) was initially generated through consumer panel and interviews regarding the most commonly used stimulants among MSM in Australia (methamphetamine, amphetamines and ecstasy), with initial administration among 98 MSM to facilitate item reduction. A community sample of 427 MSM was used to validate the SEQ‐MSM, with exploratory factor analysis (EFA; n = 202) and confirmatory factor analysis (CFA; n = 225). Results: EFA revealed three distinct substance reinforcement domains ('Enhanced sexual experience', 'Sexual communication and negotiation' and 'Cognitive impairment'). The scale was associated with stimulant consumption patterns (including greater expectancies regarding sexual enhancement among methamphetamine users), and the factor structure, comprising a final form of the MSM‐SEQ, was confirmed through CFA. Conclusions: The SEQ‐MSM represents a reliable measure of outcome expectancies related to the range of commonly used stimulants among Australian MSM. Development of applied validation studies with the SEQ‐MSM is a key next step in advancing health promotion, clinical interventions and research efforts to reduce harm (eg, HIV transmission) associated with stimulant use (particularly methamphetamine) among MSM. So what?: Objectives: This research maps expectancies specific among gay and men who have sex with men (MSM), and relationships between expectancies and stimulant use patterns and behaviours postuse – including sexual activity (eg, condomless anal sex). Summary: Substance‐related expectancies are associated with substance use and postsubstance use thoughts, feelings and behaviours. Expectancies held by specific cultural subgroups have rarely been investigated, particularly regarding a range of commonly used stimulants. The Stimulant Expectancy Questionnaire for Men who have Sex with Men (SEQ‐MSM) examines the most commonly used stimulants among MSM in Australia.